Epstein-barr virus specific immunogen - Seow, Heng Fong; Leong, Pooi Pooi; Yap, Yoke Yeow (2011)
The present invention relates to an Epstein-Barr virus specific immunogen based on the LMP2 (latent membrane protein 2) gene. Furthermore, the present invention describes variants of the immunogen as well as polynucleotides coding for the peptide-immunogen and host cells transfected with the polynucleotides. The immunogens of the present invention are specifically useful to induce an CTL immune response in patient suffering from nsaopharyngeal carcinoma. Also embodied are novel methods for the in-vitro activation of CTLs using the aforementioned immunogens.